Essentials of corporate finance - Ross, Stephen A. 1944-2017; Westerfield, Randolph; Jordan, Bradford D. (McGraw-Hill Irwin, 2004)
Examples are drawn from every aspect of business, not just corporate finance and help is given at every turn to help you look like a finance major come test time.
5. Aufl. u.d.T.: Ross, Stephen A.: Corporate finance: essentials
Keywords: Administração financeira; Bedrijfsfinanciering; Finanças das empresas; Corporations -- Finance; Corporate Finance; Finanzierung; Lehrbuch